2014
DOI: 10.1038/srep07428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MoO3(110) Crystalline Plane on Its Self-Charging Photoelectrochemical Properties

Abstract: Nanocrystalline molybdenum oxide (α-MoO3) thin films with iso-oriented crystalline layers were synthesised by the anodisation of Mo foils. Upon band-gap excitation using light illumination, α-MoO3 generates excited electrons for reductive reactions and stores some of the excited electrons in its layered crystalline structure via alkali cation intercalation. These stored electrons can be subsequently discharged from α-MoO3 to allow reductive reactions to continue to occur under non-illuminated conditions. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 24 publications
5
44
0
Order By: Relevance
“…Interestingly, photo‐responsive behavior could also be introduced into the anode for the air‐based battery, which integrated with a traditional air cathode. There are several attractive studies have been reported to demonstrate the concept to date . In 2001, Akuto et al.…”
Section: Photo‐responsive Batteries With Dual‐solid Active Materialsmentioning
confidence: 99%
“…Interestingly, photo‐responsive behavior could also be introduced into the anode for the air‐based battery, which integrated with a traditional air cathode. There are several attractive studies have been reported to demonstrate the concept to date . In 2001, Akuto et al.…”
Section: Photo‐responsive Batteries With Dual‐solid Active Materialsmentioning
confidence: 99%
“…[15] Prior to anodization, the Mo foils were degreased by sonicating twice for 10 min in acetone, followed by rinsing with acetone, ethanol, and distilled water. [15] Prior to anodization, the Mo foils were degreased by sonicating twice for 10 min in acetone, followed by rinsing with acetone, ethanol, and distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The photointercalation reaction at the electrode surface can be represented by Equation (1 where, TX 2 and TM int X 2 are nonintercalated and intercalated transition metal dichalcogenides, respectively; e − (hν) and h + (hν) are photogenerated electrons and holes; and M + solv represents the ionic species in the electrolyte which are to be intercalated. [14][15][16][17] These oxides are n-type semiconductors possessing favorable valence band potentials for oxygen evolution from water. [3][4][5][6][7] The experiments were preliminary in nature and designed to screen a wide range of potential semiconductor host compounds for solar-intercalation batteries.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the complexity of the system, our approach is to study systematically how to develop an efficient photo‐electrocatalyst for visible‐light driven photo‐electrochemical evolution of hydrogen. Instead of using any third element, we have used reduced graphene oxide as support material for Ni‐Mo, catalysts. Reduced graphene oxide can not only provide space confinement but also can control restricted growth of nanoparticles, which provide more active sites for the catalytic process.…”
Section: Figurementioning
confidence: 99%